2019 16th International Conference on the European Energy Market (EEM) 2019
DOI: 10.1109/eem.2019.8916227
|View full text |Cite
|
Sign up to set email alerts
|

Rolling Horizon Simulator for Evaluation of Bidding Strategies for Reservoir Hydro

Abstract: In this paper, a practical approach for benchmarking different bidding strategies towards the day-ahead market has been evaluated. A rolling horizon simulation framework is developed and closely integrated in the daily operations of a hydropower producer. The power producer's existing framework of decision support models and data for prices and inflow has been used to simulate the use of alternative strategies on a real life case. In the simulation procedure, a mixed-integer stochastic optimization model is us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 13 publications
0
4
0
Order By: Relevance
“…In [29], a method for measuring performance of individual historical bidding days has been proposed, where Π , in Eq.1 represents a measure of value for bidding strategy s on day d, and Π , describe the optimal value for the relevant bidding date based on a deterministic strategy with perfect foresight of price and inflow.…”
Section: Results From Historical Bidding Strategiesmentioning
confidence: 99%
See 3 more Smart Citations
“…In [29], a method for measuring performance of individual historical bidding days has been proposed, where Π , in Eq.1 represents a measure of value for bidding strategy s on day d, and Π , describe the optimal value for the relevant bidding date based on a deterministic strategy with perfect foresight of price and inflow.…”
Section: Results From Historical Bidding Strategiesmentioning
confidence: 99%
“…It is also possible to have a skewed threshold where we are more risk averse in relation to choosing one strategy opposed to another. If one strategy is to be selected, previous analysis [29] have shown that a stochastic strategy should be chosen. If a threshold of for instance 0.6 is applied, a clear tendency in direction of deterministic bidding is required before this strategy is chosen in favour of a stochastic strategy.…”
Section: Predictionmentioning
confidence: 99%
See 2 more Smart Citations